If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(6y + -2) + 4y = 2(y + 4) Reorder the terms: -2(-2 + 6y) + 4y = 2(y + 4) (-2 * -2 + 6y * -2) + 4y = 2(y + 4) (4 + -12y) + 4y = 2(y + 4) Combine like terms: -12y + 4y = -8y 4 + -8y = 2(y + 4) Reorder the terms: 4 + -8y = 2(4 + y) 4 + -8y = (4 * 2 + y * 2) 4 + -8y = (8 + 2y) Solving 4 + -8y = 8 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 4 + -8y + -2y = 8 + 2y + -2y Combine like terms: -8y + -2y = -10y 4 + -10y = 8 + 2y + -2y Combine like terms: 2y + -2y = 0 4 + -10y = 8 + 0 4 + -10y = 8 Add '-4' to each side of the equation. 4 + -4 + -10y = 8 + -4 Combine like terms: 4 + -4 = 0 0 + -10y = 8 + -4 -10y = 8 + -4 Combine like terms: 8 + -4 = 4 -10y = 4 Divide each side by '-10'. y = -0.4 Simplifying y = -0.4
| 0.20a-54.40=a | | 3z+3z=5z+2 | | 18=12x+3y | | 36b-3=o | | 128=144x-16x^2 | | -3(1-8a)=117 | | -8a-2a=6-5a-3a | | 18x^3-63x^2=9x | | 6-(-x)=-13 | | (4+2-8)*(4+5)*1876= | | -(2y-2)+4y=2(y+4) | | 38=30-3(x-1) | | -4-3(1+4x)=-37-6v | | 10(-2)+6n=12 | | -1.5x=1.5 | | 6x-4=6(x-6) | | 2+5(5x-6)=122 | | 10x+5y=550 | | .10b+15=.15b+10 | | 9.4=d+56 | | 2(x+14)=6 | | 16x^2-a^2= | | 6(5x+7)-8x=7x-33 | | .10(d)+.25(46-d)=6.70 | | -3(x-7)=-18 | | 7.7w-2.5=43.7 | | -99=-3-3(8-3n) | | 3(5a+2)=2(3a-6) | | 4(x-3)-r+2x=5(3x-7) | | 27c^3+343y^3=0 | | 5x^3-3x^2-35x+21=0 | | 60+80x=160+70x |